Influence of organizational learning, work-life balance, emotional exhaustion, and leadership style on patient safety culture among dental students - Aneizza Danya Puteri Roberto; Dewi Sri Surya Wuisan (SEAN Institute, 2024)
The purpose of this research is to analyze and test: 1. whether: Organizational learning has a positive effect on Patient Safety Culture, 2. whether Work-life balance has a positive effect on Patient Safety Culture, 3. whether Emotional Exhaustion has a positive effect on Patient Safety Culture, 4. .Does Leadership Style have a positive effect on Patient Safety Culture. The survey method used in the research carried out was data collection using a questionnaire instrument. The target research population is all professional students at RSGM-P XYZ. The number of samples determined was 160 samples. The sampling technique was carried out using purposive sampling. The Partial Least Square-Structural Equation Modeling approach with the SmartPls program was used to analyze the data. The research results show that work-life balance does not have a positive effect on Patient Safety Culture. However, organizational learning, emotional exhaustion and leadership style have a positive effect on Patient Safety Culture.